Perception and awareness artefacts and imageries in medieval European Jewish cultures - Kogman-Appel, Katrin 1958-; Baʾumgarṭen, Elishevaʿ 1969-; Hollender, Elisabeth 1965-; Shoham-Shṭainer, Efrayim 1968- (Brepols, 2023)
"What did the world look like for Jews living in medieval Europe? How did they perceive and make use of the elements of their daily life, from items on the street to religious iconography within holy spaces — in particular synagogues and at the exterior of churches — and profane elements from the home? And how did they experience the visual and material cultures of their non-Jewish neighbours? These questions form the core of this volume, which explores pre-modern Jewish approaches to images and material objects from a variety of perspectives. From clothing to manuscripts, and from lighting devices to the understanding of the invisible, the chapters gathered together in this multifaceted volume combine analyses of images and artefacts together with in-depth analyses of texts to offer fresh insights into the visual cultures that informed the world of European Jews in the Middle Ages."
Preface and Acknowledgements: "[I]n June 2017 some thirty speakers from Europe, Israel, and the United States attended a meeting at the University in Münster [...]. Several of the talks presented at that time were revised and revisited and now make up the chapters in this volume." [S. 5]
Keywords: Geschichte 500-1500; Juden; Sachkultur; Europa; Jews / Europe / History / To 1500; Material culture / Europe / History / To 1500; Material culture / Religious aspects / Judaism; Jews / Antiquities; Jews / Civilization; Jews / Intellectual life; Jewish art / Europe / History; Konferenzschrift -- 2017 -- Münster; Aufsatzsammlung